2017
DOI: 10.22216/jbe.v2i1.2104
|View full text |Cite
|
Sign up to set email alerts
|

Profitabilitas Bank Perkreditan Rakyat Di Kota Padang Di Tinjau Dari Rasio Likuiditas

Abstract: <p><em>The purpose of this study is to examine the effect of liquidity as measured by LDR (Loan to Deposit Ratio) and Loan to Asset Ratio on the profitability (Return on Asset) of Rural Bank (BPR) in Padang City. The data used are secondary data obtained by documentation method taken from publication reports of Bank Indonesia and Rural Banks in Padang City during the period of 2010 - 2015 quarter. The population used in this study are all existing BPR in Padang city and sample selection Based on pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
5
0
5
Order By: Relevance
“…However, it is found that there were only two type of analysis tools that have been used intensively by them i.e., multiple linear regression and panel data regression (Table 1). The other tool of analysis was a path analysis used by Wardani [17] Researchers who were using a multiple linear regression in their studies were Afriyeni [11]Afriyeni and Fernos [1]Agustini and Budiasih [7], Anggraeni [12], Astohar and Sumiyanti [13]Aziri et al [18], Cahyono [9] Gustika [14] Hanifa et al [19], Pandoyo [10] Pertiwi and Suardhika [20] Putri et al [2] Sari [16] Simanjuntak [21], Wardhani and Ismunawan [17] and Yuliati et al [22] Meanwhile, studies undertaken using a panel data regression were Azizah and Masdjojo [23] Maryadi and Basuki [15], Sahfitri [3] Sakat [5] and Sofyan [6] Multiple linear regression is principally easier to apply if compared to panel data regression in the context of data inputting, estimation processing, and also interpretation. These factors are probably become one of the main reasons for most of the researchers to utilize it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is found that there were only two type of analysis tools that have been used intensively by them i.e., multiple linear regression and panel data regression (Table 1). The other tool of analysis was a path analysis used by Wardani [17] Researchers who were using a multiple linear regression in their studies were Afriyeni [11]Afriyeni and Fernos [1]Agustini and Budiasih [7], Anggraeni [12], Astohar and Sumiyanti [13]Aziri et al [18], Cahyono [9] Gustika [14] Hanifa et al [19], Pandoyo [10] Pertiwi and Suardhika [20] Putri et al [2] Sari [16] Simanjuntak [21], Wardhani and Ismunawan [17] and Yuliati et al [22] Meanwhile, studies undertaken using a panel data regression were Azizah and Masdjojo [23] Maryadi and Basuki [15], Sahfitri [3] Sakat [5] and Sofyan [6] Multiple linear regression is principally easier to apply if compared to panel data regression in the context of data inputting, estimation processing, and also interpretation. These factors are probably become one of the main reasons for most of the researchers to utilize it.…”
Section: Discussionmentioning
confidence: 99%
“…a bank's performance is closely related to its functions and roles. [11] A successful bank will be able to create profit as an achievement of the management. The performance of a bank is highly dependent on the capability of the management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Masalah likuiditas harus diamati agar bank dapat menjaga kredibilitasnya. Tingkat likuiditas yang tinggi dapat menyebabkan bank tidak mampu untuk menjaga kinerja operasionalnya, maka dapat menyebabkan bank dilikuidasi (Afriyeni, 2017). Penilaian likuiditas dimaksudkan untuk mengevaluasi kemampuan Bank memelihara tingkat likuiditas yang memadai dan kecukupan manajemen resiko likuiditas (Putri & Marlius, 2018).…”
Section: Pendahuluanunclassified
“…Penggunaan profitabilitas bagi bank maupun pihak luar bank bertujuan untuk menghitung laba yang didapat oleh bank dalam periode tertentu, menilai perkembangan laba dari waktu ke waktu, serta mengukur produktifitas dari seluruh dana bank yang dipergunakan baik modal pinjaman ataupun modal sendiri. Menurut (Afriyeni, 2017) rasio profitabilitas menunjukan kemampuan manajemen perusahaan menciptakan keuntungan. Keuntungan pada tingkat yang maksimal menjadi tujuan utama dalam operasional bank.…”
unclassified